Cotton recycling: An experimental study of the mechanical preparation process - Mohammad Kanan; Bechir Wannassi; Bechir Azouz; Mohamed Ben Hassen; Ramiz Assaf; Ahmad S. Barham (Case Studies in Chemical and Environmental Engineering)
In this paper, we propose a new mechanical process (opener machine) mostly adaptive to recycle waste yarn fibers. We study the effect of the process design and the number of passages on the overall fiber quality and process yield for colored denim yarn waste. Results show that the process design has a more significant effect on the overall fiber quality than the number of passages. Better results were obtained for the process yield, fiber length, fiber strength, and fiber quality index with an opener with seven rollers OP2 compared to an opener with two rollers OP1. No significant effect was found on fiber fineness.Using an OP2 machine instead of OP1 increased: the yield by more than 150 %, mechanical properties by 5 %, Uniformity Index by 10 %, fiber mean length by 3 % and Fiber Quality Index by 9 %. It also decreases Short Fiber Count by 35 %When the number of passages is four (instead of one), the yield increased by about 55 %. the fiber mean length increased by 4 %, the Short Fiber Count decreased by 12 % and the Uniformity Index decreased by 4 %.In conclusion, the best combination for our study was obtained using the OP2 machine and four passages. This combination achieved a yield of more than 75 %, Neps = 189 Cnt/g; ML(w) = 19.6 mm; SFC = 20.6 %, UI = 63.8 %, Fineness = 146 mTex; Str = 26.3 (cN/tex)The hypothesis that mechanical process design and the number of passages in the process have an important effect on fiber quality and the process yield for colored denim yarn waste was justified.